Predicting biodiversity loss in island and countryside ecosystems through the lens of taxonomic and functional biogeography. Issue 1 (24th September 2019) - Farneda, Fábio Z.; Grelle, Carlos E. V.; Rocha, Ricardo; Ferreira, Diogo F.; López‐Baucells, Adrià; Meyer, Christoph F. J.
Abstract : We investigate how variation in patch area and forest cover quantified for three different spatial scales (buffer size of 500, 1500 and 3000 m radius) affects species richness and functional diversity of bat assemblages in two ecosystems differing in fragment–matrix contrast: a landbridge island system in Panama and a countryside ecosystem in the Brazilian Amazon. Bats were sampled on 11 islands and the adjacent mainland in Panama, and in eight forest fragments and nearby continuous forest in Brazil. Species–area relationships (SAR) were assessed based on Chao1 species richness estimates, and functional diversity–area relationships (FAR) were quantified using Chao1 functional diversity estimates measured as the total branch length of a trait dendrogram. FARs were calculated using three trait sets: considering five species functional traits (FARALL ), and trait subsets reflecting 'diet breadth' (FARDIET ) and 'dispersal ability' (FARDISPERSAL ). We found that in both study systems, FARALL was less sensitive to habitat loss than SAR, in the sense that an equal reduction in habitat loss led to a disproportionately smaller loss of functional diversity compared to species richness. However, the inhospitable and static aquatic matrix in the island ecosystem resulted in more pronounced species loss with increasing loss of habitat compared to the countryside ecosystem. Moreover, while we found a significant FARDISPERSAL for the island ecosystem in relation to forest cover within 500 m landscape buffers, FARDIET and FARDISPERSAL were not significant for the countryside ecosystem. Our findings highlight that species richness and functional diversity in island and countryside ecosystems scale fundamentally differently with habitat loss, and suggest that key bat ecological functions, such as pollination, seed dispersal and arthropod suppression, may be maintained in fragments despite a reduction in species richness. Our study reinforces the importance of increasing habitat availability for decreasing the chances of losing species richness in smaller fragments.